2012
DOI: 10.1111/j.1464-410x.2011.10706.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of androgen and oestrogen receptors and its prognostic significance in urothelial neoplasm of the urinary bladder

Abstract: OBJECTIVE• To assess the expression of the androgen receptor (AR) and oestrogen receptors (ERs) in bladder tumours because recent studies have shown confl icting results and the prognostic signifi cance of their expression remains unclear. PATIENTS AND METHODS• We investigated the expression of AR, ER α and ER β in 188 bladder tumour specimens, as well as matched 141 non-neoplastic bladder and 14 lymph node metastasis tissues, by immunohistochemistry.• We then evaluated the relationships between their expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
244
9
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 200 publications
(288 citation statements)
references
References 32 publications
32
244
9
3
Order By: Relevance
“…Indeed, a similar tendency was seen in the expression of androgen receptor (i.e. 42% in bladder tumors [10] vs. 28% in ureteral tumors [8] vs. 11% in renal pelvic tumors [8]) as well as another transcription factor GATA3 (i.e. 86% in bladder tumors [11] vs. 68% in ureteral tumors [12] vs. 36% in renal pelvic tumors [12]) we stained using the same protocol with identical antibodies.…”
Section: Discussionsupporting
confidence: 52%
“…Indeed, a similar tendency was seen in the expression of androgen receptor (i.e. 42% in bladder tumors [10] vs. 28% in ureteral tumors [8] vs. 11% in renal pelvic tumors [8]) as well as another transcription factor GATA3 (i.e. 86% in bladder tumors [11] vs. 68% in ureteral tumors [12] vs. 36% in renal pelvic tumors [12]) we stained using the same protocol with identical antibodies.…”
Section: Discussionsupporting
confidence: 52%
“…Finally, data were available from five studies on AR expression and bladder cancer susceptibility (568 tumor cases vs. 523 normal controls), six studies on AR expression and tumor grade (387 low grade vs. 663 high grade cases), nine studies on AR expression and tumor stage (582 non-invasive vs. 712 invasive cases), five studies on AR expression and RFS (414 cases) and four studies on AR expression and PFS (319 cases). The essential information of the included studies was listed in Table I ( [8][9][10][11][19][20][21][22][23][24][25][26].…”
Section: Resultsmentioning
confidence: 99%
“…Studies by Tuygun et al (19) and Mashhadi et al (22) revealed that AR expression was much higher in bladder cancer tissues, compared with 0% positivity in normal tissues. However, data from studies by Boorjian et al (9), Miyamoto et al (21) and Izumi et al (26) demonstrated that the AR positive rate was lower in bladder cancer tissues than in normal bladder samples. The present meta-analysis with five studies and 1,091 samples demonstrated no significant association between AR expression and bladder cancer susceptibility.…”
Section: Discussionmentioning
confidence: 97%
“…25,27 We and others also demonstrated the status of ER expression in bladder tumor specimens and its prognostic implications. 27,28 Although controversial, decreased and increased expression of ERα and ERβ, respectively, in higher grade and/or stage tumors has been observed. Moreover, our previous study in bladder cancer identified significant correlations between GATA3 expression and overexpression of ERα/AR or loss of ERβ overall.…”
Section: Discussionmentioning
confidence: 99%
“…Simply, in bladder cancer tissues GATA3 expression correlates with ERβ loss, an indicator of better prognosis, but with AR overexpression, an indicator of worse prognosis. 2,[25][26][27][28]31 Therefore, the clinical consequence of GATA3 loss as to tumor progression may be dependent on not only the predominance or functional activity of sex hormone receptors but also the levels of circulating sex hormones and the systemic hormonal milieu.…”
Section: Discussionmentioning
confidence: 99%